Coastal environments and global change - Masselink, Gerhard; Gehrels, W. Roland (Chichester, West Sussex ; Hoboken, NJ : American Geophysical Union, John Wiley & Sons, 2014)
"The coastal zone is one of the most dynamic environments on our planet and is much affected by global change, especially sea-level rise. Coastal environments harbour valuable ecosystems, but they are also hugely important from a societal point of view. This book, which draws on the expertise of 21 leading international coastal scientists, represents an up-to-date account of coastal environments and past, present and future impacts of global change. The first chapter of the book outlines key principles that underpin coastal systems and their behaviour. This is followed by a discussion of key processes, including sea level change, sedimentation, storms, waves and tides, that drive coastal change. The main part of the book consists of a discussion of the main coastal environments (beaches, dunes, barriers, salt marshes, tidal flats, estuaries, coral reefs, deltas, rocky and glaciated coasts and coastal groundwater), and how these are affected by global change. The final chapter highlights strategies for coping with coastal change"--Provided by publisher.
Introduction to coastal environments and global change / Gerd Masselink and Roland Gehrels -- Sea level / Glenn A. Milne -- Environmental control: geology and sediments / Edward J. Anthony -- Drivers: waves and tides / Daniel C. Conley -- Coastal hazards: storms and tsunamis / Adam D. Switzer -- Coastal groundwater / William P. Anderson, Jr. -- Beaches / Gerben Ruessink and Roshanka Ranasinghe -- Coastal dunes / Karl F. Nordstrom -- Barrier systems / Sytze van Heteren -- Tidal flats and salt marshes / Kerrylee Rogers and Colin D. Woodroffe -- Mangrove shorelines / Colin D. Woodroffe, Catherine E. Lovelock and Kerrylee Rogers -- Estuaries and tidal inlets / Duncan FitzGerald, Ioannis Georgiou and Michael Miner -- Deltas / Edward J. Anthony -- High-latitude coasts / Aart Kroon -- Rock coasts / Wayne Stephenson -- Coral reefs / Paul Kench -- Coping with coastal change / Robert J. Nicholls, Marcel J.F. Stive and Richard S.J. Tol.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Coast changes; Coastal ecology; Environmental degradation; Global warming; Coastal zone management; Water levels; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Coast changes; Coastal ecology; Coastal zone management; Environmental degradation; Global warming; Water levels; Electronic books; Electronic books